The known knowns and known unknowns of peacekeeping data - Dorussen, H; Ruggeri, A (Taylor and Francis (Routledge), 2016)
Recent literature on peacekeeping recognizes the importance of local conditions as determinants of the ‘space for peace’ and, at the same time, treats ‘bottom-up’ peacekeeping as a central criterion for its effectiveness. Accordingly, we have collected event data to analyze the impact of peacekeeping at a highly disaggregate, or local/subnational, level. Peacekeeping events are defined as data points where peacekeepers are either actors or targets of an action at a specific location and time point. Ideally time and place are recorded at the highest precision – indicating exact longitude and latitude as well as exact time of day – but often such precision remains elusive. Regardless, peacekeeping event data help to identify where peacekeepers are deployed, what they do, with whom they interact, as well as the quality of the interaction.